1968
DOI: 10.1016/s0006-3495(68)86564-6
|View full text |Cite
|
Sign up to set email alerts
|

The Thermodynamic Activity of Calcium Ion in Sodium Chloride-Calcium Chloride Electrolytes

Abstract: Experimental data on the mean activity coefficient of CaCl(2) in NaCl-CaCl(2) mixtures at ionic strengths below 1 m have been used to prepare a table of activity coefficients for Ca(++) in solutions of physiological interest. The establishment of an empirical calcium ion activity scale is discussed, and a number of possible assumptions are examined. The assumption gamma++ = (gamma+/-)(2) is suggested as being the simplest with a theoretical basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

1970
1970
2001
2001

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 11 publications
3
61
0
Order By: Relevance
“…The first is that the Na, K and Ca are fully ionized on both sides of the cell membrane. Butler (1968) has shown that this is not the case in physiological media and there may be some differences between the measurements of Na intracellular content and the activity of Na in the sarcoplasm. The second assumes that there are no assymetries in the Na-Ca exchange, whereas Glitsch et al (1970) have obtained evidence of affinity differences between the inside and outside of guinea-pig atrial muscle cells which would favour Ca efflux and Na influx.…”
Section: Discussionmentioning
confidence: 99%
“…The first is that the Na, K and Ca are fully ionized on both sides of the cell membrane. Butler (1968) has shown that this is not the case in physiological media and there may be some differences between the measurements of Na intracellular content and the activity of Na in the sarcoplasm. The second assumes that there are no assymetries in the Na-Ca exchange, whereas Glitsch et al (1970) have obtained evidence of affinity differences between the inside and outside of guinea-pig atrial muscle cells which would favour Ca efflux and Na influx.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the relative permeability to divalent cations, the GHK equation was modified to include divalent cations and activity coefficients (see Fieber & Adams, 1991). Activity coefficients of the salts were obtained from Butler (1968) and Robinson & Stokes (1965).…”
Section: Discussionmentioning
confidence: 99%
“…The calculated single ion activity coefficient of Ca 2ϩ also varies slightly with concentration of added CaCl 2 . Using the mean activity coefficient values for CaCl 2 reported in Butler (28) and the Guggenheim assumption of the Debye-Huckel theory, a ϳ20% change in single ion activity coefficient of Ca 2ϩ was calculated for solutions of ionic strength between 0.1 and 0.2 M. The EC 50 for Ca 2ϩ stimulation of CaR-dependent cytosolic calcium responses was 1 mM in our standard HEPESbuffered solution when expressed as Ca 2ϩ activity and onethird of the shift in the EC 50 , which is dependent on ionic strength, can be accounted for by these changes in Ca 2ϩ activity (28). Our data and these estimations of Ca 2ϩ activity suggest that the effects of ionic strength on CaR activation may be due to changes in the Ca 2ϩ activity at a given ionized or added Ca 2ϩ concentration as well as changes in electrostatic interactions within the receptor itself.…”
Section: Ionic Strength and The Relative Degree Of Activation For Carmentioning
confidence: 99%